PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CANVA BAGI GURU - Azzahra, Hapsah; Ardi, Ardi; Chairunnisa, Nurlaila Maysaroh (An-Nizam, 2024)
The use of learning media by utilizing technology is very important and necessary for the success of the learning process. Learning media can be visual, audio and audio-visual. Interesting learning media can create learning activities that are easy to remember and understand. Canva is a graphic design application that helps users create various types of multimedia-based teaching materials. Using Canva as a learning media can make it easier for teachers to design learning media. The aim is to hold training in making learning videos using the Canva application so that teachers are able to make videos that are interesting, easy to understand and useful and increase students' learning motivation. The methods used are socialization, training and evaluation. The existence of training activities in making learning media can improve teachers' abilities in providing material and teachers are also increasingly able to utilize technology, being able to make learning videos and get new references regarding learning media.